Bergmann's rule: a biophysiological rule examined in birds. Issue 2 (13th September 2016) - Salewski, Volker; Watt, Cortney
Abstract : The most studied ecogeographic rule is Bergmann's rule, but aspects of the original paper are often presented incorrectly even though Bergmann (1847) is explicitly cited. The goal of this paper is to 1) summarize the contents of Bergmann's paper, supported by direct translations, and 2) to discuss the main issues surrounding Bergmann's rule based on Bergmann's intentions and early definitions of the rule. Although Bergmann himself never formulated an explicit rule, based on Bergmann's (1847) intentions and early definitions of Bergmann's rule, Bergmann's rule is: "Within species and amongst closely related species of homeothermic animals a larger size is often achieved in colder climates than in warmer ones, which is linked to the temperature budget of these animals." Bergmann (1847) assumed that the surface area of an animal is a measure for heat dissipation and an animal's volume a measure of its heat production. As body size increases, an animal's surface area increases less than its volume; however, modifications in morphology and behaviour will also influence the temperature budget. Bergmann hypothesized that when everything but size is equal, the smaller animals should live in warmer areas. This was supported by empirical data on > 300 bird species belonging to 86 genera. Recommendations for use of the term Bergmann's rule include 1) inclusion of a thermoregulatory mechanism, 2) application only to homoeothermic animals, 3) but to any taxonomic group, 4) tests of the rule should test the assumption that larger animals have to produce less heat to increase body temperatures, and 5) future authors should either go back to the original publication (Bergmann 1847) when referring to it or simply not cite it at all. Synthesis Based on Bergmann's (1847) intentions and early definitions, Bergmann's rule is: "Within species and amongst closely related species of homeothermic animals a larger size is often achieved in colder climates than in warmer ones, which is linked to the temperature budget of these animals." Recommendations for use of the term Bergmann's rule include 1) inclusion of a thermoregulatory mechanism, 2) application only to homoeothermic animals, 3) and to any taxonomic group, 4) tests of the rule should examine whether larger animals have to produce less heat to increase body temperatures, and 5) authors should go back to the original publication (Bergmann 1847) when referring to it.